First record of the genus Ocyochterus from Colombia and new records of Ochteridae from Costa Rica (Hemiptera: Heteroptera) (2015)
The first Colombian record of Ocyochterus, expanding the previously known distributional range of the genus. Additionally, records of two species of Ochterus from Costa Rica are provided. The material examined is deposited at the Zoological Museum of the University of Costa Rica (MZUCR), San José, Costa Rica